Pengaruh Lingkungan Kerja dan Stres Kerja terhadap Kinerja Karyawan - Zuliatun, Nopita; Abidin, Zainal; Wahyulina, Sri; Magfirahti, Ranggaini (ALEXANDRIA (Journal of Economics, Business, & Entrepreneurship), 2024)
This research is entitled the influence of the work environment and work stress on employee performance at the East Lombok Regency Personnel and Human Resources Development Agency office. Aims to determine the influence of the work environment and work stress on employee performance. The type of research used is associative research with a quantitative approach. The data collection method used is the census method. The population and respondents in the research were 52 employees of the East Lombok Regency Personnel and Human Resources Development Agency Office. The analytical tool used is Multiple Linear Regression using SPSS version 20. The results of the analysis show that: (1) The work environment has a positive and significant effect on the performance of employees at the East Lombok Regency Personnel and Human Resources Development Agency Office. (2) Job Stress has a negative and significant effect on the performance of employees of the East Lombok Regency Personnel and Human Resources Development Agency Office